USEFUL APPROACHES TO WAREHOUSE SYSTEM AUTOMATION - Safarov Farruh Baxtiyor oʻgʻli (European Science Publishing, 2024)
This article explores various approaches to automating warehouse systems, emphasizing the benefits of each method in enhancing operational efficiency, accuracy, and overall productivity. By examining case studies and current technologies such as Automated Guided Vehicles (AGVs), Warehouse Management Systems (WMS), and robotic process automation, the research provides a comprehensive overview of best practices in warehouse automation.
Keywords: Warehouse automation, Automated Guided Vehicles (AGVs), Warehouse Management Systems (WMS), robotics, process optimization, efficiency.